Analysis of MSW full-scale facilities based on anaerobic digestion and/or composting using respiration indices as performance indicators. (July 2017) - Colón, J.; Ponsá, S.; Álvarez, C.; Vinot, M.; Lafuente, F.J.; Gabriel, D.; Sánchez, A.
Graphical abstract: Highlights: Six full-scale waste treatment plants were analysed in terms of their performance. Dynamic and cumulative respiration indices were used for the entire monitoring. Mechanical pretreatment, anaerobic digestion and composting were the main stages. Plants relying on anaerobic digestion plus composting achieved a high performance. Plants relying only on composting showed, on average, a poor performance. Abstract: The Landfill Directive (1999/31/EC) forces European States to reduce the amount of biodegradable municipal waste landfilled to 35% of 1995 levels. Mechanical-Biological Treatment (MBT) plants are the main alternative to waste incineration and landfilling. In this work, the waste treatment efficiency of six full-scale MBT facilities has been analysed using respiration indices (Dynamic Respiration Index and Cumulative Oxygen Consumption) to monitor plant performance. MBTs relying on anaerobic digestion plus composting achieved a high grade of stability on final compost (0.24 ± 0.09 mg O2 g −1 DM h −1 and 20 ± 9 mg O2 g −1 DM for dynamic respiration and cumulative consumption, respectively). On the contrary, MBTs relying only on composting showed a poor performance (1.3 ± 0.2 mg O2 g −1 DM h −1 and 104 ± 18 mg O2 g −1 DM for dynamic respiration and cumulative consumption, respectively). These results highlight the usefulness of respirometric balances to assess the performance of MBT full-scale plants.